PENINGKATAN DAN PENGEMBANGAN POTENSI UMKM DARI HASIL PERTANIAN DESA SUKADANA, KECAMATAN BAYAN, KABUPATEN LOMBOK UTARA - Yadnya, Made Sutha; Ardi , Salman; Riksa , Anggara; Fajrina , Baiq Zatil Hidayah; Sugiartini , Ni Nengah Cista Nanda; Hidayati , Laely; Priadana , Wahyu; Utami , Ida Ayu Tresna Dewi; Sugiarta , Anya Putri; Hayat , Nahriyatul; Haekal , Muhammad (Universitas Mataram, 2023)
Sukadana Village, Bayan District, North Lombok Regency is a village that has abundant resources such as honey, cassava, fish, cashew nuts, corn, and so on. One of the mainstay commodities is honey and cassava. However, the abundance of available potential has not been optimally utilized by residents. Like the less attractive packaging used in Trigona Honey products. In addition, the lack of product innovation resulting from processed cassava makes cassava have a low selling value so an increase in agricultural products needs to be accompanied by appropriate and efficient marketing. The lack of innovation and creativity of the residents is an obstacle to increasing agricultural output in Sukadana Village. Therefore, we have the opportunity to provide innovations to improve agricultural output, such as innovating packaging for Trigona Honey products, innovating cassava agricultural products, and marketing outreach to MSMEs in Sukadana Village. It is hoped that with this, residents will be moved to continue businesses related to these two products.